Reversible phosphorylation of proteins in proliferating and differentiating cells : cyclic variations and the effect of growth regulators - Ferreira, Gracinda Maria Nunes (My University, 1994)
Living cells are highly auto-dynamic entities which means that the underlying biochemistry is equally dynamic, a reality which is ignored by most researchers. Theoretical studies indicate that such a state must be due to the existence of oscillatory variations in the levels and activities of key components in the cell. In this study, the dynamic behaviour of four major, interrelated areas of cell biochemistry (phosphorylation, dephosphorylation, the terminal reaction of glycolysis and the amount of soluble protein) were examined and all systems found to oscillate in murine erythroleukaemic cells (MEL) and, where examined, also in the human HL-6Q leukaemic cell line. certain processes have been shown to be oscillatory for the first time ( phosphorylation potential, the lactate dehydrogenase active isozyme level and aspects of the regulation thereof). While others have been shown to occur at a higher frequency than previously reported (phosphotyrosine phosphatase activity, the activity and apparent isozyme pattern of lactate dehydrogenase, the amount of extractable protein). All rhythms are shown (for the first time) to be complex and to involve several contributing periodicities, some modulating the period and amplitude of the observed oscillation. The frequencies are very high (periods of 1-20 minutes and probably Less) and the amplitudes are equally high (variations in magnitude of as much as a hundred fold). Phosphorylation processes, currently of particular interest with regard to the nature and control of cell proliferation are thus found to be more highly dynamic than previously believed, a fact which throws some doubt on the current ideas on cell proliferation. The actual lactate dehydrogenase (LDH) active isozyme pattern is shown not to be constant (as generally believed) but to vary at high frequency (possibly due to phosphorylation of the the enzyme) while the kinetics and specificity of the lone isozyme in murine erythroleukaemic cells appear to be varying at equally high frequency due to the action of regulators (perhaps arising elsewhere within the glycolytic pathway). Similar results were obtained with HL-60 leukaemic cells with at least two of the isozymes varying in level, to some extent independently. The hormone, insulin, and the inducer of cell differentiation, HMBA (hexamethylenebisacetamide), have been found to affect the dynamics of the four systems although, because of the complexity of the rhythms the actual effects on the dynamics are not easily defined. Insulin has a marked effect on the mean level of the activity of the LDH isozyme. The fact that all oscillations are seen despite no attempt being made to synchronise the cell population suggests the existence of communication between cells but how this can occur when the rhythms are of such high frequency is intriguing. All the results add further support for the long standing view of my supervisor, that the properties and behaviour of cells reflect the internal dynamics and that differentiation, cancer and intracellular signalling occur through changes in the pattern of temporal organisation of cellular oscillations.
A Dissertation Submitted to the Faculty of Science University of the Witwatersrand, Johannesburg In fulfilment of the requirements for the Degree of Doctor of Philosophy
Keywords: Protein Kinases; Phosphorylation; Growth regulators